Practical Feed Estimation - Matthew C (Massey University)
Measuring machines Why farmers measure cover; Ways to measure cover (Plate / Probe / Visual / CDAX); Controlling variability. Practical feed estimation Intake estimation from pre- and post grazing mass; Supplementary matters: rotation length vs animal intake, pasture growth, & pasture quality.